Addressing industrial air pollution in Kazakhstan : reforming environmental payments policy guidelines - Organisation for Economic Co-operation and Development (OECD green growth studies, ISSN 2222-9515, 2019)
Summary.
Keywords: kestävä kehitys : Kazakstan; ympäristönsuojelu : Kazakstan; ilmansuojelu : Kazakstan; ympäristöpolitiikka : Kazakstan; teollisuus : Kazakstan; ympäristövaikutukset : Kazakstan; ympäristömaksut : Kazakstan